Understanding digital transformation in the manufacturing industry: a systematic literature review and future trends - Abdallah, Yasser Omar; Shehab, Essam; Al-Ashaab, Ahmed (Instituto de Inovação e Gestão de Desenvolvimento de Produto, 2021)
Digital transformation is one of the most evolving areas both in the research literature and in industrial applications. No doubt that this process will be crucial in the survival of any manufacturing organisation in the future, especially during the current COVID-19 crisis. This paper aims to present a review of the concept in the manufacturing industry through the literature currently available on the topic. The literature was classified, and the results of each study were analysed. From this review, six critical findings have been identified in this paper. First, this paper proposes a definition of Digital Transformation and its concept development in the manufacturing industry. Moreover, significant challenges that exist in the manufacturing industry in the implementation of the digital transformation process have been classified as well as the major enabling technologies that help to implement the Digital Transformation. Finally, the benefits of implementing Digital Transformation in the manufacturing industry and its impact on the manufacturing ecosystem have been highlighted. Following a comprehensive review of the literature, future research directions are formulated to identify abundant research opportunities.
Keywords: digital transformation; manufacturing; literature review